The Role of Institutional Mechanisms in Conflict Management in a Multipolar World: A Futuristic Study - Suleiman Mahmoud, Lect. Dr. Ady (Basra studies journal, 2026)
In light of the decline of unilateral hegemony, conflict management has become increasingly linked to the effectiveness of international and regional institutions in containing crises. This research seeks to clarify the conceptual framework of conflict management and distinguish it from the concepts of settlement and final resolution of crises. It also analyzes the legal and institutional foundations of the roles of the United Nations, the Security Council, the International Court of Justice, and regional organizations. The research problem stems from a central question regarding the effectiveness of these mechanisms and their future prospects in a multipolar world. To address this issue, the study adopts an analytical approach to deconstruct institutional structures, and a foresight (future-oriented) approach to explore emerging trends. The study concludes that institutional mechanisms retain their significance; however, their effectiveness is constrained by power competition and the veto system. It also finds that the Security Council alone is no longer capable of ensuring effective management of complex conflicts. In contrast, there is an increasing and complementary role for regional organizations, international judicial bodies, and flexible peaceful mechanisms. The research further concludes that the future of conflict management requires deep institutional reform and stronger integration between international and regional levels. It also recommends activating preventive and foresight-based mechanisms to make the international system more flexible and adaptable to future transformations.